Assisted dying challenges: Dynamic and stasis in the UK courts: Conway v. Secretary of State for Justice. (December 2018) - Hobson, Clark
This commentary reviews the High Court Decision in Conway v. Secretary of State for Justice . Mr Conway's argument, that section 2(1) Suicide Act is incompatible with his right of respect for his private life under Article 8(1) European Convention on Human Rights, adopted as a Convention right for the purposes of the Human Rights Act 1998, was dismissed. The comment discusses four themes arising from the case. First, it examines how the High Court attempts to distinguish claimants who can act to end their own lives, such as Mr Conway, from individuals who cannot carry out any act to commit suicide. This distinction is arguably morally arbitrary and runs counter to principles of equal concern and respect. Second, Mr Conway puts forward an alternative statutory scheme with specific procedural criteria, designed to safeguard relevant competing legitimate interests; to protect the weak and vulnerable while legalizing assisted suicide in certain circumstances. However, the nature of Mr Conway's argument regarding this alternative statutory scheme misses the point. It is possible for a court to find the current legislative measure, section 2(1) Suicide Act, to disproportionately interfere with a claimant's Article 8(1) right in principle, without having to be satisfied there is a future legislative measure that does better balance competing legitimate interests. Third, the comment shall consider the High Court's reasoning behind holding that Nicklinson was not binding insofar as deciding Mr Conway's case. Finally, the ethical nuance of the court's consideration of the aim of section 2 shall be considered briefly.